The evaluation of gestational age concerning placental thickness and fetal parameters using ultrasonography - Shukla, Kamlesh Kumar; Kumar Jha, Arvind; Jee, Kanhaiya (Brazilian Journal of Biometrics, 2025)
The ultrasound parameters are very important factors for the estimation of gestational age (GS) decreases as pregnancy advances in age. Therefore, it is essential to reconnoiter other parameters that may complement the established fetal biometric parameters in predicting GS, especially in late pregnancy. The main objective of this study is to determine the relationship between GS and sonographic placental thickness (PL) as well as fetal parameters for the second (21-30 weeks) and third trimesters (31-40 weeks) using regression analysis. The mean scores for PL, GS, and weight of fetal were found 2.56±0.38 cm, 165.15±15.60 days and 654.31±266.68 gm respectively for 21-30 weeks. Similarly mean scores were found to correspond to fetal parameters for 31-40 weeks. The relationship between GA (Y) in days and PT & BPD in cm. In the 21-30 weeks, and GS 21-30 weeks = 146.36+7.70PL 21-30 weeks = 74.03+15.8BPD 21-30weeks. The relationship between GS and fetal parameters (BPD, AC, FL, etc.) are obtained as follows: GS 21-30 weeks=124.96+1.49BPD-0.34HC+0.54AC-0.61FL-1.2PL+0.05Weight. Gestational age has been estimated using two regression lines, first using three variables and second using all fetal parameters. It has been observed that Gestational age can be estimated accurately using all fetal parameters for both periods (21-30 & 31-40 weeks).